Improving safety of salami by application of bacteriocins produced by an autochthonous Lactobacillus curvatus isolate. (April 2015) - de Souza Barbosa, Matheus; Todorov, Svetoslav Dimitrov; Ivanova, Iskra; Chobert, Jean-Marc; Haertlé, Thomas; de Melo Franco, Bernadette Dora Gombossy
Abstract: The aims of this study were to isolate LAB with anti- Listeria activity from salami samples, characterize the bacteriocin/s produced by selected isolates, semi-purify them and evaluate their effectiveness for the control of Listeria monocytogenes during manufacturing of salami in a pilot scale. Two isolates (differentiated by RAPD-PCR) presented activity against 22 out of 23 L. monocytogenes strains for bacteriocin MBSa2, while the bacteriocin MBSa3 inhibited all 23 strains in addition to several other Gram-positive bacteria for both antimicrobials and were identified as Lactobacillus curvatus based on 16S rRNA sequencing. A three-step purification procedure indicated that both strains produced the same two active peptides (4457.9 Da and 4360.1 Da), homlogous to sakacins P and X, respectively. Addition of the semi-purified bacteriocins produced by Lb. curvatus MBSa2 to the batter for production of salami, experimentally contaminated with L. monocytogenes (10 4 –10 5  CFU/g), caused 2 log and 1.5 log reductions in the counts of the pathogen in the product after 10 and 20 days respectively, highlighting the interest for application of these bacteriocins to improve safety of salami during its manufacture. Highlights: Isolation of bacteriocin producing Lactobacillus curvatus from Italian type salami. Isolates were identified as Lb. curvatus based on 16S rRNA sequencing. Both strains expressed bacteriocins, homologous to sakacins P and X, respectively. Presence of sakacin P encoding gene have been recorded in both studied strains. Lb. curvatus MBSa2 bacteriocin been used for control of Listeria monocytogenes in salami.